Burkholderia cepacia: An Outbreak in the Peritoneal Dialysis Unit. Issue 1 (January 2019) - Gleeson, Sarah; Mulroy, Eoin; Bryce, Elizabeth; Fox, Sally; Taylor, Susan L.; Talreja, Hari
Burkholderia cepacia is a ubiquitous, opportunistic, environmental gram-negative bacillus which most commonly affects cystic fibrosis and immunocompromised patients. Rarely, it can cause peritoneal dialysis (PD) exit-site infection (ESI). Information relating to predisposing factors, clinical course, and treatment options for B. cepacia ESIs is limited. Although reports of B. cepacia healthcare-associated infections exist, outbreaks in PD units have not previously been reported. A recent outbreak of B. cepacia ESI in our PD unit provided a unique opportunity to study B. cepacia ESIs and to outline an approach to investigating such an outbreak. After unexpectedly identifying B. cepacia as the cause of PD catheter ESIs in 3 patients over an 11-week period, we began systematically screening our PD population for B. cepacia exit-site colonization. A further 6 patients were found to be affected, 3 with asymptomatic colonization and 3 with symptomatic B. cepacia ESI. Four of the 6 developed tunnel infections requiring multiple courses of antibiotic treatment, and 3 patients required catheter removal; 2 patients with symptomatic ESIs without tunnel involvement responded to oral and topical antibiotics. Further investigation implicated 4% chlorhexidine aqueous bodywash used by all patients as the probable source of the outbreak. This is the first reported outbreak of B. cepacia ESIs. We noted an association between diabetes mellitus and refractory/more extensive infection. Our experience suggests that isolated ESIs can be treated successfully with oral antibiotics whereas tunnel infections generally require catheter removal.